Molecular mechanism governing the plasticity of use-dependent spike broadening in dorsal root ganglion neurons - Tyler D. Alexander; Stephen Tymanskyj; Kyle J. Kennedy; Leonard K. Kaczmarek; Manuel Covarrubias (Proceedings of the National Academy of Sciences, 2025)
Use-dependent spike broadening (UDSB) results from inactivation of the voltage-gated K + (Kv) channels that regulate the repolarization of the action potential. However, the specific signaling and molecular processes that modulate UDSB have remained elusive. Here, we applied an adeno-associated viral vector approach and dynamic clamping to conclusively demonstrate how multisite phosphorylation of the N-terminal inactivation domain (NTID) of the Kv3.4 channel modulates UDSB in rat dorsal root ganglion (DRG) neurons. The Kv3.4 phosphonull variant promotes slow recovery from inactivation, cumulative inactivation, and UDSB. In contrast, the Kv3.4 phosphomimic variant promotes fast recovery from inactivation and robust resistance to cumulative inactivation and UDSB. Furthermore, knocking down Kv3.4 maximizes AP width and eliminates UDSB modulation. Together with the evidence from previous work, the results concretely suggest how dynamic UDSB modulation governed by multisite phosphorylation of the NTID of Kv3.4 in DRG neurons may play a significant role in mechanosensory transduction and pain modulation.